Clinical utility of simultaneous measurement of alpha-fetoprotein and des-γ-carboxy prothrombin for diagnosis of patients with hepatocellular carcinoma in China: A multi-center case-controlled study of 1,153 subjects - Zheng, Shuguo; Sugawara, Yasuhiko; Zhang, Keming; Hasegawa, Kiyoshi; Li, Qiang; Kokudo, Norihiro; Feng, Xiaobin; Ma, Kuansheng; Song, Tianqiang; Inagaki, Yoshinori; Zhao, Xin; Wang, Zhigang; et al. (BioScience Trends, 2014)
This study aimed to investigate the clinical utility of simultaneous measurement of alphafetoprotein (AFP) and des-γ-carboxy prothrombin (DCP) for hepatocellular carcinoma (HCC) diagnosis in Chinese patients predominantly caused by hepatitis B virus infection by a multi-center case-controlled study. Subjects were 1,153 individuals from three major hospitals in China, including 550 cases in HCC group, 164 in Malignant disease group, 182 in Benign disease group, 85 in Chronic liver disease group, and 173 in Normal group. Serum levels of AFP and DCP were measured and clinicopathological features were determined for all subjects. Results showed that the levels of DCP and AFP were significantly higher in HCC group (550 patients, 74.18% with HBV infection) than that in other four groups (P < 0.001). Receiver operating curves (ROC) indicated the optimal cut-off value was 86 mAU/mL for DCP with a sensitivity of 71.50% and specificity of 86.30%, and 21 ng/mL for AFP with a sensitivity of 68.00% and specificity of 93.20%. The area under ROC curve was 0.846 for DCP, 0.832 for AFP, and 0.890 for the combination of DCP and AFP. The combination of DCP and AFP resulted in a higher Youden index and a sensitivity of approximately 90%, even for small tumors. The simultaneous measurement of AFP and DCP could achieve a better sensitivity in diagnosing Chinese HCC patients, even for small tumors.